First degree fudge - DeSmet, Christine (DeSmet, Christine. Fudge shop mystery., 2013)
Between getting her store up and running and uneasily settling back into her charming Lake Michigan hometown, Ava Oosterling has her plate full. She hopes using local fresh dairy and her own flavorful imagination to cook up one-of-a-kind fudge will also create a brand-new start for her. And if she can tempt wealthy ex film star Rainetta Johnson to try her newest creation, Cinderella Pink, at a local fund raiser, maybe her road to big time success will be short and sweet. But when Rainetta chokes to death on a stolen diamond hidden in the fudges fluffy depths, Ava is pegged as the prime suspect. Now saving her business and reputation means investigating a batch of townspeople who had numerous reasons to hate disdainful, hard bargaining Rainetta. With Avas best friend and her former flame in the suspect mix, she must figure out who the real culprit is fast or face a very bitter end.